Sistem Ketatanegaraan Ideal Menurut Ibnu Abi Rabi’ - Gafur, Abdul; Hasan, Ahmadi; Umar, Masyithah; Khasyi'in, Nuril (Interdisciplinary Explorations in Research Journal, 2024)
Abstract Ibn Abi Rabi's perspective on the concept of the state fundamentally differs from the thoughts of Greek philosophers like Plato and Aristotle, primarily due to the strong integration of the Islamic worldview in his thinking. While Ibn Abi Rabi’ agrees with Plato that a leader should be someone respected in society, he prefers monarchy as the best system of governance. He argues that leadership by a single king or ruler can maintain political stability and unity better than other forms of government such as aristocracy, oligarchy, democracy, and demagoguery, which can lead to chaos if citizens irresponsibly exercise their political rights. According to Ibn Abi Rabi’, the basis of a king's authority stems from religious teachings, particularly the Qur’an (QS. al-An’am: 165), which states that a king's power and authority are a mandate from God. He sets forth six criteria for an ideal king: paternalistic ties to the previous king, noble aspirations, precise and strong vision, resilience in facing challenges, substantial wealth, and loyal assistants, without emphasizing Quraysh lineage. Ibn Abi Rabi’ also identifies four main pillars in the formation of a state: the head of state, justice, the people, and management. By fulfilling these four pillars, he believes that the state will achieve political stability and strength. Keywords: system, constitutional, ideal, ibnu Abi Rabi' Abstrak Pandangan Ibn Abi Rabi’ mengenai konsep negara memiliki perbedaan mendasar dengan pemikiran para filosof Yunani seperti Plato dan Aristoteles, terutama karena integrasi kuat dari worldview Islam dalam pemikirannya. Ibn Abi Rabi’ sependapat dengan Plato bahwa pemimpin haruslah seseorang yang dihormati di masyarakat, namun ia lebih memilih bentuk pemerintahan monarki sebagai sistem yang terbaik. Menurutnya, kepemimpinan oleh satu orang raja atau penguasa tunggal mampu menjaga kestabilan dan persatuan politik negara, dibandingkan dengan sistem pemerintahan lainnya seperti aristokrasi, oligarki, demokrasi, dan demagogi yang dapat menyebabkan kekacauan jika warga negara menyalahgunakan hak politiknya. Dasar otoritas raja menurut Ibn Abi Rabi’ bersumber dari ajaran agama, khususnya Al-Qur’an QS. al-An’am: 165, yang menyatakan bahwa kekuasaan dan otoritas raja adalah mandat dari Tuhan. Ia menetapkan enam syarat bagi calon raja yang ideal, yaitu hubungan paternalistik dengan raja sebelumnya, aspirasi luhur, pandangan yang tepat dan kuat, ketahanan dalam menghadapi tantangan, kekayaan besar, dan pembantu setia, tanpa menekankan keturunan Quraisy. Ibn Abi Rabi’ juga mengemukakan empat pilar utama dalam pembentukan negara: kepala negara, keadilan, rakyat, dan pengelolaan. Dengan terpenuhinya keempat pilar tersebut, ia meyakini bahwa negara akan menjadi stabil dan kuat secara politis. Kata kunci : sistem, ketatanegaraan, ideal, ibnu Abi Rabi’